SOLUTIONS FOR FOLLOW-UP ON CONSTITUTIONAL COURT DECISIONS THAT ARE FINAL AND BINDING IMPLEMENTATIVE - Irfan Aditya (NOMOI Law Review, 2023)
Indonesia has been through 4 times of constitution changing, started from 1999 to 2002. The amendment has created a few of the country's new institutions, such as a Constitutional Court of Indonesian Republic. The final decision that the Constitutional Court made turns out to have a few of the Constitutional Court that is not obeyed. Hence, it's not aligned with the nature of the Constitutional Court itself. This research is made to know how is the solution to the follow-up of the Constitutional Court's decision that is final and binding implementative. The method of this research is the normative law research with the statue approach. The source of the data that is used is a secondary data with primary legal material, secondary legal materials and tertiary legal materials, data analysis was carried out using the qualitative methods. The results show there are several factors that caused the Constitutional Court Decision to not be implemented, which are: the Constitutional Court as a negative legislature; no decision executive institution; there is no grace period to carry out the decision; and there are no juridical consequences for ignoring the decision. Therefore, the solution is to form an executive working unit for decisions under the Registrar's Office of the Constitutional Court to provide coercive power to the parties concerned and if the Constitutional Court Decisions are still not complied with and enforced, then the related parties will be subject to sanctions.